Using farmers' ex ante preferences to design agri-environmental contracts: A systematic review - Christoph Schulze; Katarzyna Zagórska; Kati Häfner; Olimpia Markiewicz; Mikołaj Czajkowski; Bettina Matzdorf (Journal of Agricultural Economics, 2023)
Ensuring that farmers' ex ante preferences are accounted for is crucial for the design of effective agri-environmental contracts. We present a systematic review of 127 discrete choice experiment (DCE) studies of farmers' preferences with respect to agri-environmental contracts. DCE studies evaluate two central features of farmers' behaviour: (1) their willingness to accept land use prescriptions, such as fertiliser use, application of pesticides, restrictions on cropping, livestock management, integration of silvopasture, maintaining soil health or water use restrictions; and (2) their responses to variations in incentive and commitment criteria, such as reward schemes, monitoring regimes, technical assistance, flexibility of agreements, administrative burden and collaborative implementation. Our analysis considers how these different elements are interlinked and applied in experiments to simulate farmers' decision-making processes. We examine recent methodological improvements in explaining farmer behaviour, including the accommodation of preference heterogeneity, the combining of discrete (enrolment) and continuous decisions, and the incorporation of farmers' sense of identity. DCEs have been applied for the ex ante analysis of different policy instruments to inform the European Common Agricultural Policy and agri-environmental schemes outside the EU. The results of this systematic review may be useful in informing the future design of such agri-environmental programmes. The database underpinning this systematic literature review may help peer scientists to (a) compare, validate and triangulate their own findings with respect to other experimental approaches, (b) use previous willingness-to-accept (WTA) measures as priors for their own study design, and (c) identify research gaps regarding farmers' preferences for agri-environmental measures.
Keywords: 630; agri-environmental contracts; agri-environmental policy; choice modelling; discrete choice experiments; environmental governance; ex ante evaluation; stated preferences